Full Duplex AF and DF Relaying Under Channel Estimation Errors for V2V Communications - Siye Wang; Dandi Wang; Chao Li; Wenbo Xu (IEEE Access, 2018)
In this paper, we investigate the outage performance of full-duplex (FD) and half-duplex (HD) vehicle to vehicle (V2V) networks. We consider two vehicular communication scenarios with the assistance of roadside unit (RSU), i.e., RSU-to-vehicle-to-vehicle (RVV) and vehicle-to-RSU-tovehicle (VRV) scenarios. In particular, we analyze the outage performance of vehicular networks with the amplify-and-forward (AF) and decode-and-forward (DF) protocols under the effect of residual loopback-interference (LBI) and channel estimation errors. For RVV scenario, the upper bounds for the outage probability of the AF based FD and HD relaying over double Rayleigh fading channels are derived. Moreover, we derive the approximate closed form expressions for the outage probability of the DF based FD and HD relaying protocol over Rayleigh fading channels; For VRV scenario, the exact closed-form expressions for the outage probability of the AF and DF relaying protocols are presented in case of FD and HD modes. Furthermore, we derive the approximate closed-form expressions for the outage probability of hybrid FD/HD mode on AF and DF relaying protocols. The numerical and simulation results corroborate our theoretical ones and quantify the impact of the data rates, channel estimation errors and the residual LBI on the system performance.